2017
DOI: 10.11648/j.ijdsa.20170304.12
|View full text |Cite
|
Sign up to set email alerts
|

A New Variant of the SEIZ Model to Describe the Spreading of a Rumor

Abstract: Abstract:We propose a variant of the SEIZ mathematical model originally proposed by Bettencourt et al, where the rumor spreads between two different scenarios and which do not share information with each other. This model is studied analytically where we include a new parameter for forgetting a rumor. We show results that were obtained using this model for a certain case in Venezuela. Finally, we also provide the numerical code for the numerical integration in order to provide a useful tool for others in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A empirical study by Jin et al, using the SEIZ model developed by Bettencourt et al from the earlier SIR model, showed excellent agreement with Twitter social media traffic [58, 59]. Isea and Lonngren extended the SEIZ model to describe rumour propagation [60]. Zhao et al have studied other variations of the SIR model in rumour spreading [6163].…”
Section: Methodsmentioning
confidence: 99%
“…A empirical study by Jin et al, using the SEIZ model developed by Bettencourt et al from the earlier SIR model, showed excellent agreement with Twitter social media traffic [58, 59]. Isea and Lonngren extended the SEIZ model to describe rumour propagation [60]. Zhao et al have studied other variations of the SIR model in rumour spreading [6163].…”
Section: Methodsmentioning
confidence: 99%
“…They also proposed a ratio R SI , the transition rates entering E from S to the transition rates exiting E to I, to differentiate rumor and real news events data. Isea and Lonngren [83] extended the SEIZ model by considering a forgetting rate of rumor posts. The forgetting rate is defined as a probability a user forgets the rumors across all the states.…”
Section: ) Epidemic Modelsmentioning
confidence: 99%
“…The methodology required to solve the system of equations proposed in this work has been described on multiple occasions throughout various scientific works [10][11][12][13][14], and for this reason, only we shows the results.…”
Section: Analytical Resolutionmentioning
confidence: 99%